2023
DOI: 10.1111/1471-0528.17631
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐trimester uterine artery Doppler for aspirin discontinuation in pregnancies at high risk for preterm pre‐eclampsia: Post‐hoc analysis of StopPRE trial

Abstract: ObjectiveTo assess whether aspirin treatment can be discontinued in pregnancies with normal uterine artery pulsatility index (≤90th percentile) at 24–28 weeks.DesignPost‐hoc analysis of a clinical trial.SettingNine maternity hospitals in Spain.Population or SamplePregnant individuals at high risk of pre‐eclampsia at 11–13 weeks and normal uterine artery Doppler at 24–28 weeks.MethodsAll participants received treatment with daily aspirin at a dose of 150 mg. Participants were randomly assigned, in a 1:1 ratio, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…Recent studies have suggested that it may be possible to stop aspirin at 28 weeks’ gestation if the angiogenic ratio (sFlt-1:PlGF) and/or the UtAPI are normal [ 254 , 255 ]. Mendoza et al performed a multicenter, open-label, randomized trial of 936 pregnant women who were identified as being at high risk of preterm PE during first-trimester screening (StopPRE trial) [ 254 ].…”
Section: Identification Assessment and Management Of Women With Pcos ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have suggested that it may be possible to stop aspirin at 28 weeks’ gestation if the angiogenic ratio (sFlt-1:PlGF) and/or the UtAPI are normal [ 254 , 255 ]. Mendoza et al performed a multicenter, open-label, randomized trial of 936 pregnant women who were identified as being at high risk of preterm PE during first-trimester screening (StopPRE trial) [ 254 ].…”
Section: Identification Assessment and Management Of Women With Pcos ...mentioning
confidence: 99%
“…Bonacina et al performed a post hoc analysis of the StopPRE trial described above [ 255 ]. In this secondary analysis, women with a UtAPI greater than the 90th percentile were excluded.…”
Section: Identification Assessment and Management Of Women With Pcos ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Dear Dr. Papageorghiou, Bonacina et al report the results of a post-hoc analysis of the StopPRE trial. 1,2 In the trial, women identified by screening at 11-13 weeks of gestation as being at high risk for preterm pre-eclampsia (PE) were treated with aspirin (150 mg/day).…”
mentioning
confidence: 99%